PENYEDIAAN SARANA INFORMASI CERITA SEJARAH DALAM BAHASA INGGRIS DI DAERAH WISATA ‘KAMPUNG HERITAGE KAYOETANGAN’ MALANG – JAWA TIMUR - Kusumawardani, Irene Nany (Faculty of Cultural Studies, Universitas Brawijaya, 2021)
The development of tourism in Malang City should be balanced with improvements in communication skills, particularly foreign languages (English) for tourism operators and tourism facilities that can communicate basic information to foreign tourists, such as directions and descriptions/stories about a tourist spot. Kampung Heritage Kayoetangan (KHK) as one of the thematic village tourist destinations in Malang City requires historical information facilities that can narrate the origins and cultural heritage of the historical spots located there. Therefore, this community service initiative was conducted to assist in providing historical storytelling information facilities at KHK, thereby adding value so that tourism practitioners there can better communicate the historical significance of the places they inhabit.